Kant on Empirical and Transcendental Functions of Memory (2020)
This paper analyses the features of Kant’s view of memory, which Kant himself described explicitly in his lectures on anthropology and implicitly in the A edition of the Critique of Pure Reason. I shall offer a review of literature on Kant’s view of memory up to this day. I suggest that memory is a cognitive faculty that has the power to store and reproduce representations. Kant distinguishes among three different kinds of memorization which are relevant for human cognition. I offer reasons to hold that imagination and memory must be differentiated by their functioning, although the first one grounds the second one. Finally, I hold that certain functions of memory need to be presupposed at a transcendental level, in which memory would play a fundamental function with regard to the possibility of experience